Odorant Metabolism Catalyzed by Olfactory Mucosal Enzymes Influences Peripheral Olfactory Responses in Rats - Thiebaud, Nicolas; Veloso Da Silva, Stéphanie; Jakob, Ingrid; Sicard, Gilles; Chevalier, Joëlle; Ménétrier, Franck; Berdeaux, Olivier; Artur, Yves; Heydel, Jean-Marie; Le Bon, Anne-Marie (PLOS ONE, 2013)
A large set of xenobiotic-metabolizing enzymes (XMEs), such as the cytochrome P450 monooxygenases (CYPs), esterases and transferases, are highly expressed in mammalian olfactory mucosa (OM). These enzymes are known to catalyze the biotransformation of exogenous compounds to facilitate elimination. However, the functions of these enzymes in the olfactory epithelium are not clearly understood. In addition to protecting against inhaled toxic compounds, these enzymes could also metabolize odorant molecules, and thus modify their stimulating properties or inactivate them. In the present study, we investigated the in vitro biotransformation of odorant molecules in the rat OM and assessed the impact of this metabolism on peripheral olfactory responses. Rat OM was found to efficiently metabolize quinoline, coumarin and isoamyl acetate. Quinoline and coumarin are metabolized by CYPs whereas isoamyl acetate is hydrolyzed by carboxylesterases. Electro-olfactogram (EOG) recordings revealed that the hydroxylated metabolites derived from these odorants elicited lower olfactory response amplitudes than the parent molecules. We also observed that glucurono-conjugated derivatives induced no olfactory signal. Furthermore, we demonstrated that the local application of a CYP inhibitor on rat olfactory epithelium increased EOG responses elicited by quinoline and coumarin. Similarly, the application of a carboxylesterase inhibitor increased the EOG response elicited by isoamyl acetate. This increase in EOG amplitude provoked by XME inhibitors is likely due to enhanced olfactory sensory neuron activation in response to odorant accumulation. Taken together, these findings strongly suggest that biotransformation of odorant molecules by enzymes localized to the olfactory mucosa may change the odorant’s stimulating properties and may facilitate the clearance of odorants to avoid receptor saturation.